Field intubation in civilian patients with hemorrhagic shock is associated with higher mortality. Issue 2 (February 2016) - Chou, Daisy; Harada, Megan Y.; Barmparas, Galinos; Ko, Ara; Ley, Eric J.; Margulies, Daniel R.; Alban, Rodrigo F.
Abstract : BACKGROUND: Field intubation (FI) by emergency medical service personnel on severely injured trauma patients remains a contentious practice. Clinical studies suggest an association between FI and adverse outcomes in patients with traumatic brain injury. Military tactical emergency casualty care recommends deferring intubation and providing supplemental oxygenation until reaching a more equipped destination. In addition, animal models with penetrating hemorrhagic shock demonstrate increased acidosis with intubation before resuscitation. The purpose of this study was to evaluate the impact of FI on outcomes in trauma patients with hemorrhagic shock requiring massive transfusion. METHODS: The Los Angeles County Trauma System Database was retrospectively queried for all trauma patients 16 years or older with hemorrhagic shock requiring massive transfusion (≥6 U packed red blood cells in the first 24 hours) between January 1, 2012, and June 30, 2014. Demographics, clinical and transfusion data, and outcomes were compared between patients who received FI and those who did not (NO-FI). Multivariate regression analysis was used to adjust for confounders. RESULTS: Of 552 trauma patients meeting inclusion criteria, 63 (11%) received FI, and the remaining 489 (89%) were NO-FI. Age, sex, and incidence of blunt injury were similar between the FI and the NO-FI group. The FI cohort presented with a lower median Glasgow Coma Scale (GCS) score (3 vs. 14, p < 0.001), a lower median systolic blood pressure (86 mm Hg vs. 104 mm Hg, p < 0.001), and a higher median Injury Severity Score (ISS) (41 vs. 29, p < 0.001). Mortality was significantly higher in FI patients (83% vs. 43%, p < 0.001). Transfusion patterns and total field times were similar in both groups. After adjusting for confounders, FI patients had increased odds of mortality (adjusted odds ratio, 2.89; 95% confidence interval, 1.08–7.78; p = 0.035). In addition, FI was identified as an independent predictor of mortality (adjusted odds ratio, 3.41; 95% confidence interval, 1.35–8.59; p = 0.009). CONCLUSION: FI may be associated with higher mortality in trauma patients with hemorrhagic shock requiring massive transfusion. Less invasive airway interventions and rapid transport might improve outcomes for these patients. LEVEL OF EVIDENCE: Therapeutic study, level IV; epidemiologic study, level III.